Linfluence De La Desirabilite Percue Et De La Faisabilite Percue Sur La Formation De Lintention Entrepreneuriale Des Diplomes De Lenseignement Superieur Au Cameroun (Global Journal of Management and Business Research, 2020)
Abstract not found
Keywords: perceived desirability; perceived feasibility; entrepreneurial intentions; graduates